2022
DOI: 10.1900/rds.2022.18.146
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis and its Severity Predictors in Type 1 Diabetic Children; A 10-year Experience of A Teaching Hospital in Saudi Arabia

Abstract: OBJECTIVE: Our objective was to determine the trend and precipitating factors of the severity of diabetic ketoacidosis (DKA) in the population admitted to the Pediatric Intensive Care Unit (PICU) in a large teaching hospital in the Eastern region of Saudi Arabia. METHODS: We conducted a retrospective, analytical study at King Fahad Hospital, Imam Abdulrahman Bin Faisal University, Alkhobar, Saudi Arabia. We retrieved the complete medical records of 2234 children who were admitted to the PICU during the 10-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Conversely, Peng et al, reported that mild DKA was the most prevalent (Peng, Wei, et al 2021). Abdominal discomfort was the most common symptom (78.3% [n=141]), followed by vomiting (73.9% [n=133]), and nausea (32.2% [n=58]), corroborating the findings of other studies (Robert, Asirvatham Alwin, et al 2018, Albuali, Waleed H., andMohammad H. Al-Qahtani 2022). No mortality was reported in this study, which is attributed to the adoption of clear protocols for diagnosing and treating hospitalized patients.…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, Peng et al, reported that mild DKA was the most prevalent (Peng, Wei, et al 2021). Abdominal discomfort was the most common symptom (78.3% [n=141]), followed by vomiting (73.9% [n=133]), and nausea (32.2% [n=58]), corroborating the findings of other studies (Robert, Asirvatham Alwin, et al 2018, Albuali, Waleed H., andMohammad H. Al-Qahtani 2022). No mortality was reported in this study, which is attributed to the adoption of clear protocols for diagnosing and treating hospitalized patients.…”
Section: Discussionsupporting
confidence: 70%